Exercise intensity and pacing strategy of cross-country skiers during a 10 km skating simulated race - Formenti, D.; Rossi, A.; Calogiuri, G.; Thomassen, T. O.; Scurati, R.; Weydahl, A. (Research in Sports Medicine, 2015)
The aim of this study was to observe the cardiovascular demands by monitoring the heart rate (HR) and the pacing strategy by evaluating the speed during a simulated cross-country skiing race. Eleven skiers (16.45 ± 1.67 yrs; 21.32 ± 2.03 kg m-2; 72.35 ± 4.69 mL min-1 kg-1) competed in a 10km event divided into four laps. The HR profile was classified into four intensity zones. The skiers spent 66.84 ± 23.64% and 31.82 ± 23.77% of the total time above 90% and at 80 - 90% of the HRmax respectively, whereas the lower zones were negligible. During the event, a progressive increase in intensity was observed: HRmean raised by 2.42% in the last versus the first lap (p < 0.001). The skiers decreased their speed in the second (p = 0.017) and the third laps (p < 0.001) compared to with the first lap. In the fourth lap the skiers increased the speed slightly but without statistical difference. The speed maintained by the skiers resulted in the adoption of a reverse J-shaped pacing strategy.